Pathway-oriented action of dietary essential oils to prevent muscle protein oxidation and texture deterioration of farmed rainbow trout. (18th February 2019) - Santos, H. M. C.; Méndez, L.; Secci, G.; Parisi, G.; Martelli, R.; Medina, I.
Abstract : Recently, great attention has been directed towards the use of essential oils from aromatic plants as antimicrobials and antioxidant in food matrix. Fish is well known to be a high perishable food. Indeed, fish muscle is susceptible to suffer protein and lipid oxidation during frozen storage, which can lead to the development of softening and undesirable volatile molecules. However, the possible inclusion of essential oils in fish feed for preserving fish flesh quality during storage is still unclear. For this reason, the potential protective effects of the incorporation of a dietary essential oil constituted by eucalyptol, carvacrol and thymol, to rainbow trout's ( Oncorhynchus mykiss ) feed were here investigated. Frozen fish fillets resulting from trout fed the essential oil showed a significant protection of specific muscle proteins against the oxidation produced during frozen storage at –10ºC for 6 months. Essential oil-enriched feed decreased carbonylation of specific myofibrillar ( α -actinins-1 and -3, myosin heavy chain, myomesin-1, pyruvate kinase, tropomyosin, troponin-T and actin) and sarcoplasmic proteins (glycogen phosphorylase, creatine kinase, fructose-bisphosphate aldolase A and phosphoglycerate mutase 2). Essential oils also increased actin stability and preserved muscle protein solubility and water holding capacity. In addition, essential oils inhibited the onset of lipid oxidation and rancidity, resulting in frozen fish with superior textural quality and sensory scores. As a final conclusion, the inclusion of essential oils in farmed rainbow trout feed is largely efficient for increasing fish quality and shelf life during frozen storage, mainly through a selective-antioxidant effect on muscle proteins.